Antibacterial and anti-biofilm activities of cinnamaldehyde against S. epidermidis. (January 2019) - Albano, Mariana; Crulhas, Bruno Pereira; Alves, Fernanda Cristina Bérgamo; Pereira, Ana Flávia Marques; Andrade, Bruna Fernanda Murbach Teles; Barbosa, Lidiane Nunes; Furlanetto, Alessandra; Lyra, Luciana Pupo da Silveira; Rall, Vera Lúcia Mores; Júnior, Ary Fernandes
Abstract: The search for new antimicrobial drugs has been necessary due to the increased bacterial resistance to antibiotics currently in use, and natural products play an important role in this field. The aim of this study was to evaluate the in vitro effect of cinnamaldehyde on S. epidermidis strains, biofilm set-up prevention, as well as its effect on pre-established biofilms. The minimum inhibitory concentration (MIC) ranged from 300 to 500 μg/mL, and the minimum bactericidal concentration (MBC) from 400 to 600 μg/mL. The biofilm inhibitory concentration and biofilm eradication concentration values were four-fold (clinical isolate) and eight-fold (ATCC strain) greater than the concentration required to inhibit planktonic growth. Sub-inhibitory concentrations of cinnamaldehyde attenuated biofilm formation of S. epidermidis strains on polystyrene microtiter plates. The combination of cinnamaldehyde and linezolid was able to inhibit S. epidermidis with a bactericidal effect. Further investigation of the mechanism of action of cinnamaldehyde revealed its effect on the cell membrane permeability, and confocal laser scanning microscopy (CLSM) images illustrated the impact of cinnamaldehyde in the detachment and killing of existing biofilms. Thereby, our data confirmed the ability of cinnamaldehyde to reduce bacterial planktonic growth of S. epidermidis, inhibiting biofilm formation and eradicating pre-formed biofilm. Graphical abstract: Highlights: Subinhibitory concentrations of cinnamaldehyde attenuated biofilm formation of S. epidermidis. Cinnamaldehyde MIC values ranged from 300 to 500 μg/mL. Biofilm eradication concentrations were fourfold and eightfold greater than that required to inhibit planktonic cells. Synergism was observed among cinnamaldehyde and linezolid.